2016
DOI: 10.4068/cmj.2016.52.1.1
|View full text |Cite
|
Sign up to set email alerts
|

HDAC and HDAC Inhibitor: From Cancer to Cardiovascular Diseases

Abstract: Histone deacetylases (HDACs) are epigenetic regulators that regulate the histone tail, chromatin conformation, protein-DNA interaction, and even transcription. HDACs are also post-transcriptional modifiers that regulate the protein acetylation implicated in several pathophysiologic states. HDAC inhibitors have been highlighted as a novel category of anti-cancer drugs. To date, four HDAC inhibitors, Vorinostat, Romidepsin, Panobinostat, and Belinostat, have been approved by the United States Food and Drug Admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
302
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(306 citation statements)
references
References 98 publications
3
302
0
1
Order By: Relevance
“…Both HAT and HDAC inhibitors are being tested for control of cancer cells in clinical trials, but they have also been shown to play a role in controlling cardiac hypertrophy in animal models. 26,27 The evidence that inhibiting both global activators and repressors has beneficial effects in cardiac stress strongly supports the hypothesis that control of transcription flexibility, and not the exact gene expression per se, may be an effective therapy to manage already progressing cardiac stress.…”
Section: Targeting Transcription In Left Ventricular Hypertrophymentioning
confidence: 74%
“…Both HAT and HDAC inhibitors are being tested for control of cancer cells in clinical trials, but they have also been shown to play a role in controlling cardiac hypertrophy in animal models. 26,27 The evidence that inhibiting both global activators and repressors has beneficial effects in cardiac stress strongly supports the hypothesis that control of transcription flexibility, and not the exact gene expression per se, may be an effective therapy to manage already progressing cardiac stress.…”
Section: Targeting Transcription In Left Ventricular Hypertrophymentioning
confidence: 74%
“…Preclinical atherosclerosis models have suggested that drugs modulating histone acetylation may be utilized to treat cardiovascular disease in the future 52. It is noteworthy that, to date, there are some debates on the effects of HDAC inhibitors in treating experimental atherosclerosis 50. Moreover, the side effects of HDAC inhibitor on the vascular system need to be systematically and closely monitored 50.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibitors are becoming a well-known class of drugs for cancer treatment, in particular after the FDA approval of Vorinostat and Romidepsin for the treatment of hematologic cancers (2). At least 12 different HDACis are currently in use for clinical trials, and more are being sought to augment chemotherapy (4, 5, 7), immunotherapy/ cancer vaccines (14) and overcome multi-drug resistance which are common to diverse cytostatic or receptor-mediated drugs (3,8,9,(36)(37)(38) HDAC inhibitors were first isolated from microorganisms, and continue to be developed from microbial metabolites (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of HDACs are evident in advanced malignancy, where inhibitors (HDACis) antagonize tumor growth (2,3) antagonize tumor growth (2,3), augment chemotherapy (4-7), reverse chemoresistance (3,8,9), attenuate metastasis, halt epithelial-mesenchymal transition (10)(11)(12) and block tumor immune evasion (13,14). With the overwhelming surge of HDACis being sought worldwide for nearly every type of cancer (e.g.…”
mentioning
confidence: 99%